(3GdYHQ aj NHQ ef ZHQs - (3eMeO Hf CMeO Hf YKeGf Hf bGjeGR GdPgHj, TeS GdOjf, CHh YHO Gddg,J (B748 (3g` s ((3OeTb s)
(3ChdgG (B:s
(3HYO agPG JGQjN eNJUQ Ydi GdSfhGJ, CPcQ ajg eG jbOQ di ef CTgQ GdMhGOK hGdhajGJ s
(3GfXQ Qbe (B733 (3JGQjNs
(3fSNI KGfjIs
(3fSNI NRGFfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs